Bulk analysis by resequencing and RNA‐seq identifies candidate genes for maintaining leaf water content under water deficit in maize. Issue 4 (23rd September 2021) - Zhang, Fengqi; Zhang, Jun; Ma, Zhiyan; Xia, Laikun; Wang, Xiangyang; Zhang, Lanxun; Ding, Yong; Qi, Jianshuang; Mu, Xinyuan; Zhao, Faxin; Ji, Tianhui; Tang, Baojun
Abstract: Drought is one of the main abiotic stresses adversely affecting maize growth and grain yield. Identifying drought tolerance‐related genes and breeding varieties with enhanced tolerance are effective strategies for minimizing the effects of drought stress. In this study, the leaf relative water content (LRWC) was used for evaluating drought tolerance. QTL‐seq analysis of 419 F2 individuals from a cross between ZhengT22 (the drought‐tolerant line with high LRWC) and ZhengA88 (the drought‐sensitive line with low LRWC) revealed four LRWC‐related QTLs ( qLRWC2, qLRWC10a, qLRWC10b, and qLRWC10c ) in maize seedlings under water deficit. Of these QTLs, qLRWC2 was located in a 2.03‐Mb interval on chromosome 2, whereas qLRWC10a, qLRWC10b, and qLRWC10c were located in 2.85‐, 3.99‐, and 2.05‐Mb intervals, respectively, on chromosome 10, and the 93 genes contained the variation loci locating in the four QTLs regions. To identify the candidate genes within the QTLs, an RNA‐seq analysis was performed for the parents exposed to water deficit. Seven genes with effective variation loci showed significant difference in expression either in ZhengA88 or ZhengT22 in response to water deficit. Moreover, among the genes, ZmPrx64, ZmCIPK, HSP90, and ABCG34 have all been shown to be related to water stress in the previous studies. Thus, they are primary considered as the potential candidate genes controlling LRWC under water deficit at the seeding stage of maize in this study. These findings will help clarify the molecular basis of drought tolerance in maize seedlings and may be relevant for future functional analysis and for breeding drought‐tolerant maize varieties.